Effects of classroom debate and socratic method on critical thinking and speaking ability of Malaysian undergraduate ESL learners - Zare, Pezhman (2016)
The present research is an attempt to study the effects of classroom debate and Socratic Method on critical thinking and speaking ability of Malaysian undergraduate ESL learners. In addition, the study tries to determine which of these two methods is more effective in developing the participants‘ critical thinking and speaking ability. Furthermore, students‘ perceptions and feedbacks are investigated and explored toward these two methods. The study adopts a quasi-experimental mixed method design (pre-test, post-test design) in which both quantitative and qualitative methods of data collection is employed. The participants of the study consisted of an intact class of thirty two undergraduate students doing TESL at the Faculty of Educational Studies, Universiti Putra Malaysia. The participants had completed two years of their degree program; the class was selected based on purposive sampling. The New Jersey Test of Reasoning Skills (NJTRS) and content analysis method (Newman et al., 1995) were administered to assess the learners‘ critical thinking skills at the beginning and at the end of the study. Participants‘ speaking ability was measured at the beginning and at the end of the study. To triangulate the data, semi-structured interviews were conducted to investigate the students‘ perceptions on the two teaching methods of the study. In addition, the participants provided their responses to a number of open-ended questions. Furthermore, ongoing observations were made to monitor the developments in participants‘ behavior and the classroom atmosphere. Based on the findings, the learners‘ critical thinking showed improvement after going through classroom debates and Socratic discussions for nine and ten sessions respectively. Both classroom debate and Socratic Method were equally effective in improving the participants‘ critical thinking. The participants‘ speaking ability showed significant progress after going through the classroom debates and Socratic discussions. Classroom debate, however, showed to be more effective in improving speaking ability. The research participants also found the two methods of the study innovative, interesting, constructive, and helpful to teaching and learning. The respondents also believed that participating in classroom debate and/or Socratic discussions helped them overcome the fear of talking before a crowd, boost their confidence to talk and express their opinions, improve their speaking ability, and enhance their critical thinking skills.